2018
DOI: 10.5057/ijae.ijae-d-17-00032
|View full text |Cite
|
Sign up to set email alerts
|

How does Congruence of Scent and Music Affect People's Emotions

Abstract: It is widely believed that there is a relationship between scent and music. For example, there is congruence among certain scent, music, and consumers' buying behaviors according to previous study. However, only limited number of scents and music have been analyzed, which is not sufficient to conclude common characteristics of congruence between scent and music in arousal dimension. Consequently, we investigated the effect of scent on the mood evaluation of music by using four kinds of scents and two music sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Thus, the result of the present study supports the findings of these previous studies. Additionally, a similar trend of change in the mean value in Preference and Combination was observed as same as the result of a previous study [19]. However, unexpectedly, the higher points of the good combinations were found in incongruent conditions: condition 2 with low arousal music and high arousal scent, and condition 3 with high arousal music and low arousal scent.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, the result of the present study supports the findings of these previous studies. Additionally, a similar trend of change in the mean value in Preference and Combination was observed as same as the result of a previous study [19]. However, unexpectedly, the higher points of the good combinations were found in incongruent conditions: condition 2 with low arousal music and high arousal scent, and condition 3 with high arousal music and low arousal scent.…”
Section: Discussionsupporting
confidence: 89%
“…The reason why the higher points were obtained in conditions 2 and 3 is difficult to explain, and there must be a complicated relationship between music and scent. For example, although Zhou et al had a careful preliminary experiment for selecting scents, inverted trends on impression were observed in the two arousal scents for one music piece [19]. A recent study has tried to extract common dimensions on the impression of different type of stimuli including music and scent [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was revealed that the congruent combination of scent and music in terms of arousal significantly raise consumers' satisfaction of the retail store, and booster impulse buying behaviors [6]. Similarly, arousal congruent combination of scent and music is claimed to enhance the experience of music appreciation [7]. In addition, it was reported that the scent of orange sweet generates positive influence on sound sleep, and refreshed wakeup among aged females [8].…”
Section: Introductionmentioning
confidence: 99%